Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1155/2021/6624347
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory and Antimicrobial Activities of Compounds Isolated from Distichochlamys benenica

Abstract: Distichochlamys benenica is a native black ginger that grows in Vietnam. In point of fact, there is limitation of available information in the literature making mention of the chemical constituents and bioactive properties of this plant. This study is aimed at isolating trans-o-coumaric acid (1), trans-cinnamic acid (2), and borneol (3) from the rhizomes of D. benenica Q.B.Nguyen & Škorničk and evaluate the anti-inflammatory and antimicrobial activities of 1-3 using the carrageenan paw edema model and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 43 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…These phytochemicals are likely to contribute to various medicinal uses as well as nutritional supplementations of the herbs. Hithermost, only the plant family Distichochlamys benenica has been reported for the acetylcholinesterase inhibitory effect of its rhizome essential oil (Hoang et al 2020 ) and the anti-inflammatory and antibacterial activities of its isolated compounds (Pham et al 2021 ). Further than that, this work is the first time the biological effects of Distichochlamys citrea are reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…These phytochemicals are likely to contribute to various medicinal uses as well as nutritional supplementations of the herbs. Hithermost, only the plant family Distichochlamys benenica has been reported for the acetylcholinesterase inhibitory effect of its rhizome essential oil (Hoang et al 2020 ) and the anti-inflammatory and antibacterial activities of its isolated compounds (Pham et al 2021 ). Further than that, this work is the first time the biological effects of Distichochlamys citrea are reported in the literature.…”
Section: Resultsmentioning
confidence: 99%
“…Carrageenan had been exploited with antimicrobial, antiviral, and anticancer activity. The current research observed a significant interaction of the carrageenan with multiple targets resulting majorly around −7 to −6 Kcal/mol binding score [ 28 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…The general conditions of Desmond were established according to the previous study. 36 The solvent model was set with a flexible simple point-charge water model with the OPLS3e force field. 50 nanoseconds (ns) and 50 picoseconds (ps) were set as the total simulation time and the trajectory recording interval, respectively.…”
Section: Experimental Methodsmentioning
confidence: 99%